Natural Gomesin-like Peptides with More Selective Antifungal Activities - Ilia A. Bolosov; Ekaterina I. Finkina; Ivan V. Bogdanov; Victoria N. Safronova; Pavel V. Panteleev; Tatiana V. Ovchinnikova (Pharmaceutics)
Background: Antimicrobial peptides are generally considered promising drug candidates for combating resistant bacterial infections. However, the selectivity of their action may vary significantly. Natural gomesin, isolated from haemocytes of the tarantula Acanthoscurria gomesiana, demonstrates a broad spectrum of antimicrobial activities, being the most effective against pathogenic fungi. Methods: Here, we searched for variants of natural gomesin-like peptides and produced their recombinant analogs in the bacterial expression system. The antimicrobial activities of the obtained peptides were tested against a panel of bacterial and yeast strains, and their toxicity towards human cells was examined. Results: Most of the new analogs of gomesin have primary structures homologous to that of the natural gomesin; however, they have fewer amino acid residues and post-translational modifications. One of the discovered analogs, the His-rich shorter peptide from the spider Dysdera sylvatica, designated as DsGom, displays antifungal activity comparable with that of natural gomesin. In the process of the structural–functional study of DsGom, it was shown that this analog retains a basic mechanism of action similar to that of natural gomesin. The DsGom analog has a significantly better toxicity profile as compared to gomesin. At the same time, the loss of the first Arg residue reduces, but does not annul, the antifungal activity of DsGom. Moreover, the acidification of the growth medium reduces the loss of the antifungal activity of this analog. Conclusions: The discovered natural gomesin-like peptides display more selective antifungal activities as compared to gomesin. The low cytotoxicity of DsGom, combined with its high antifungal activity and stability, allows us to consider it a promising drug candidate for the treatment of fungal infections, especially those caused by fungi of the Candida genus.